Campus crime: legal, social, and policy perspectives - Fisher, Bonnie S.; Sloan, John J. (Charles C Thomas, Publisher, Ltd., 2022)
"This new edition of Campus Crime shares with readers the advancements that have been made in understanding campus crime. In the three sections of this book, the chapters in each section review changes while also addressing current - and even future - crime and security issues confronting institutions with higher educations (IHEs). Some of these chapters address long-standing topics such as the sexual victimization of college women and the role of campus police departments in securing IHEs. Other chapters address new issues in campus crime such as drugging victimization, concealed carrying of firearms on campus, and "technology-based" security issues such as the challenges posed by cybercriminals, as well as activities like cyberstalking and identity theft that involve campus community members both as victims and offenders. Although there are new topics and contributors to this edition, the previously covered chapters have been updated as well. The authors have brought together contributors who could provide both a current picture and critical analysis of issues concerning the legal, social, security, and policy contexts of campus crime. The chapters review topics at hand, offer substantive, critical analyses, thought-providing discussion, and raise relevant policy issues, questions, and answers. This fourth edition combines seasoned campus crime experts with those relatively new to the study of campus crime who represent the next generation of scholars and practitioners in the field and bring with them the passion that comes with beginning to address what they see as the issues, explanations, solutions for, and responses to campus crime"--